Organic and solution-processed tandem solar cells with 17.3% efficiency - Meng, Lingxian; Zhang, Yamin; Wan, Xiangjian; Li, Chenxi; Zhang, Xin; Wang, Yanbo; Ke, Xin; Xiao, Zuo; Ding, Liming; Xia, Ruoxi; Yip, Hin-Lap; Cao, Yong; et al. (Science (American Association for the Advancement of Science), 2018)
Tandem solar cells can boost efficiency by using a wider range of the solar spectrum. The bandgap of organic semiconductors can be tuned over a wide range, but, for a two-terminal device that directly connects the cells, the currents produced must be nearly equal. Meng et al. used a semiempirical analysis to choose well-matched top- and bottom-cell active layers. They used solution processing to fabricate an inverted tandem device that has a power conversion efficiency as high as 17.4%. Science , this issue p. 1094 A semi-empirical analysis helped to optimize materials for a tandem organic solar cell with high power conversion efficiency. Although organic photovoltaic (OPV) cells have many advantages, their performance still lags far behind that of other photovoltaic platforms. A fundamental reason for their low performance is the low charge mobility of organic materials, leading to a limit on the active-layer thickness and efficient light absorption. In this work, guided by a semi-empirical model analysis and using the tandem cell strategy to overcome such issues, and taking advantage of the high diversity and easily tunable band structure of organic materials, a record and certified 17.29% power conversion efficiency for a two-terminal monolithic solution-processed tandem OPV is achieved.